Researching Ancient Colours in Museums Collections: Best Possible Practices and Prospects - Barandoni, Cristiana (Actual Problems of Theory and History of Art, 2024)
With this contribution, we intend to retrace all the salient phases adopted by the writer and the research groups involved starting from 2014 to date regarding the experimentation and search for an ideal method to be able to communicate the ancient colours in Greek and Roman sculptures. The cognitive path, which began in 2014 at the Uffizi Galleries, thanks to the following two and a half years, has ensured the structuring of a method of cognitive approach to ancient polychromy. Considering the activities at the Galleries definitively concluded, it was decided to set up a new working group that would put into practice the results obtained from the analysis of the experimentation with a stable and continuous museum method. In 2018, a new chapter of the project was launched at the National Archaeological Museum of Naples whose conceptual, theoretical, and practical structure retraces in its entirety the guidelines adopted previously: for this reason, this contribution, ample space will be given to the Florentine three-year period in favour of a greater understanding of the cognitive processes currently adopted in Naples, without whose preliminary discussions they would not be clear or understandable.